Oral health status and its impact on academic performance of young adolescents in Jazan, Saudi Arabia - Quadri, Mir Faeq Ali (2022)
Apart from the physical and psychosocial impact, oral diseases in children have been linked to poor school performance that influences later life potential. Earlier studies have examined a range of oral health conditions using various clinical and subjective measures; nevertheless, there is a lack of empirical evidence and discussion explaining the pathway model of any specific oral health condition leading to poor academic performance. The current thesis hypothesized that dental caries, which operates through toothache, can disrupt learning activities and result in poor performance at school. Two studies, one cross-sectional and one case-control were carried out on two non-overlapping samples of schoolchildren aged 12-14 years in Jazan, Saudi Arabia. The outcome measures were a pass/fail GPA grade and teacher perception of the child’s academic performance. The exposure parameters comprised the common oral health conditions in children, which were assessed by clinical examinations and a self-perceived questionnaire. The relationships between poor oral health-impacted sleep and study activities, and academic performance were also assessed. The findings of both studies were consistent in showing that dental caries, gingivitis, plaque deposits, toothache, tooth discolouration, and oral health impacts that are related to sleeping and studying were significantly associated with academic performance. The finding also showed that dental caries is the most likely oral health condition that can be linked to poor academic performance. The odds of failing the examination were between 3-6 times greater for every unit increase in decay severity (OR boys = 3.09; 95%CI: 2.25, 4.25, OR girls = 3.23; 95%CI: 2.48, 4.19 in the cross sectional study) (OR boys = 6.34; 95%CI: 3.82, 10.50, OR girls = 5.26; 95%CI: 2.86, 9.66 in the case-control study). Subsequent mediation analysis found two models indicating the indirect effect of caries on academic performance. Toothache and impacted sleep (Boys: bootstrap 95%CI: 0.02, 0.29) (Girls: bootstrap 95% CI 1.37, 12.81) and toothache and impacted study activity (Girls: bootstrap 95% CI 0.10, 0.82) were the significant mediators in the two-mediator pathway analysis. The investigation of a causal relationship using the Bradford Hill criteria had further supported the pathway models; the direct effect of dental caries on academic performance lacks rationale and the pathway through the mediators explain the relationship better. Thus, the findings of this thesis supported the hypothesis that dental caries has a role in explaining poor academic performance in children and it operates through mediators including toothache, and impaired sleep and study activities.